2019
DOI: 10.29374/2527-2179.bjvm094319
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Clinical and Epidemiological aspects of dairy cows naturally infected by Trypanosoma vivax in the states of Pernambuco and Alagoas, Brazil

Abstract: Trypanosoma vivax is the most pathogenic hemoparasite of ruminants, causing huge economic losses to the producer when prevalent in the herd. This study aims to characterize the trypanosomiasis in naturally infected cattle in order to assess the clinical findings, epidemiological risk factors, and diagnosis of this disease in outbreaks occurring in the states of Pernambuco and Alagoas, northeastern Brazil. For this purpose, historical and clinical examinations, blood collection and clinical monitoring were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
2
0
3
Order By: Relevance
“…The acquisition of adult animals from endemic regions justifies the higher occurrence of this disease in this category. This condition may have contributed both to the entry of the parasite into local properties and to the dissemination of the parasite between animals of the same herd, as already widely mentioned in the literature (91,92,96) . However, in Paraiba, outbreaks of the disease in cattle coincided with an increase in the number of vectors (90,94) .…”
Section: Trypanosomiasismentioning
confidence: 72%
“…The acquisition of adult animals from endemic regions justifies the higher occurrence of this disease in this category. This condition may have contributed both to the entry of the parasite into local properties and to the dissemination of the parasite between animals of the same herd, as already widely mentioned in the literature (91,92,96) . However, in Paraiba, outbreaks of the disease in cattle coincided with an increase in the number of vectors (90,94) .…”
Section: Trypanosomiasismentioning
confidence: 72%
“…In Brazil, the expanding geographic distribution of T. vivax has resulted from the livestock moving between endemic regions and those where the conditions are favorable (climate favorable to hematophagous dipterans, animals lacking prior immunity to the parasite, and the permanent practice of sharing blood-contaminated needles [fomites] during vaccination and application of oxytocin) (Cadioli et al, 2012;Bastos et al, 2017;Andrade Neto et al, 2019). The results showed that cows are significantly more exposed to T. vivax compared to calves, which may be related to the longer period in contact with hematophagous mechanical vectors and fomites (especially due to shared needles).…”
Section: Discussionmentioning
confidence: 99%
“…A aquisição de animais adultos de regiões endêmicas, justifica a maior ocorrência desta enfermidade nessa categoria. Essa condição pode ter contribuído tanto para a entrada do parasita nas propriedades locais, como para a disseminação do parasita entre animais do mesmo rebanho, assim como já é amplamente citado na literatura (91,92,96) . Entretanto, na Paraíba surtos da doença em bovinos coincidiram com o aumento no número de vetores (90,94) .…”
Section: Tripanossomíaseunclassified